Assessing Radiation Emergency Preparedness Planning by Using Community Assessment for Public Health Emergency Response (CASPER) Methodology. Issue 3 (6th June 2014) - Nyaku, Mawuli K.; Wolkin, Amy F.; McFadden, Jevon; Collins, Jim; Murti, Michelle; Schnall, Amy; Bies, Shane; Stanbury, Martha; Beggs, Jennifer; Bayleyegn, Tesfaye M.
Abstract: Introduction: Approximately 1.2 million persons in Oakland County, Michigan (USA) reside less than 50 miles from the Fermi Nuclear Power Plant, Unit 2, but information is limited regarding how residents might react during a radiation emergency. Community Assessment for Public Health Emergency Response (CASPER) survey methodology has been used in disaster and nondisaster settings to collect reliable and accurate population-based public health information, but it has not been used to assess household-level emergency preparedness for a radiation emergency. To improve emergency preparedness plans in Oakland County, including how residents might respond during a radiation emergency, Oakland County Health Division (OCHD), with assistance from the Centers for Disease Control and Prevention (CDC) and the Michigan Department of Community Health (MDCH), conducted a CASPER survey. Methods: During September 2012, a 2-stage cluster sampling design was used to select 210 representative households in Oakland County. By using in-person surveys, the proportion of households with essential needs and supplies, how residents might respond to public health authorities' instructions, and their main source for obtaining information during a radiation emergency were assessed. Data were weighted to account for the complex sampling design. Results: Of the goal of 210 households, 192 (91.4%) surveys were completed: 64.7% and 85.4% of respondents indicated having 3-day supplies of water and of nonperishable food, respectively; 62.8% had a 7-day supply of prescription medication for each person who needed it. Additionally, 64.2% had a working carbon monoxide detector; 67.1% had a first-aid kit; and 52% had an alternative heat source. In response to instructions from public health officials during a radiation emergency, 93.3% of all respondents would report to a radiation screening center; 96% would evacuate; and 91.8% would shelter-in-place. During a radiation emergency, 55.8% of respondents indicated their main information source would be television, 18.4% radio, and 13.6% the Internet. The most trusted source for information would be the local public health department (36.5%), local news (23%), a physician (11.2%), and family members (11.1%). Including completed and incomplete interviews, refusals, and nonrespondents, 517 total households were contacted. Conclusions: CASPER data regarding how residents might react during a radiation emergency provided objective and quantifiable information that will be used to develop Oakland County's radiation emergency preparedness plans. Survey information demonstrates the feasibility and usefulness of CASPER methodology for radiation emergency preparedness planning. MK Nyaku, AF Wolkin, J McFadden, J Collins, M Murti, A Schnall, S Bies, M Stanbury, J Beggs, TM Bayleyegn .Assessing radiation emergency preparedness planning by using Community Assessment for Public Health Emergency Response (CASPER) methodology .Prehosp Disaster Med .2014 ;29 (3 ):1 -9 .